Young children's experiences of living with a parent with bipolar disorder: Understanding the child's perspective. (19th July 2016) - Backer, Clare; Murphy, Rebecca; Fox, John R. E.; Ulph, Fiona; Calam, Rachel
Abstract : Objectives: To explore the experiences of young children of living with a parent with bipolar disorder (BD) and how this impacts on their emotional well‐being. Design: Qualitative study using a computer‐assisted semi‐structured interview, 'In My Shoes' (IMS). Methods: Ten children aged between 4 and 10 years with a parent with BD identified via self‐help groups were interviewed about their experience of family life. Thematic analysis was used following transcription. Results: Four main themes emerging from thematic analysis were as follows: perception of parents; knowledge and awareness of BD; managing family life with a 'bipolar' parent; and living in a family with BD. Four‐year‐old children could participate in the IMS interviews and discuss their parent's mood, behaviour, and mental health. Children had candid and insightful discussions about their parent's BD including symptoms and parenting, and could reflect on how having a parent with BD affected them emotionally and practically. Older children were better able to articulate their parent's illness and its impact. Conclusions: This exploratory study represents an important step in examining directly experiences of young children whose parents have BD. Using IMS, it was possible to gather insightful information from children to generate hypotheses and influence service development. Children of all ages had some knowledge and understanding of their parent's illness, describing both positive and negative experiences in the family. Further research to build understanding of children's perspectives and the support they feel they and their family would benefit from would enhance the development of appropriate services and interventions. Practitioner points: Using age‐appropriate tools, it is possible to elicit the views of young children about their parent's mental health and parenting. Young children have insight into the impact of bipolar disorder in the family on themselves and family members.